2022
DOI: 10.1186/s13256-022-03255-4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal tetanus with good outcomes at a regional referral hospital in Eastern Uganda: a case report

Abstract: Background Neonatal tetanus, though now rare in developed countries, is still a significant cause of mortality in developing countries. Mortality, which can be as high as 100% without medical intervention, can be reduced to less than 10% with intensive care. Low-resource settings still lack sophisticated intensive care that has been shown to improve outcomes in high-income countries. However, there are low-cost interventions that have been shown to improve outcomes such as the use of magnesium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Neonatal tetanus is also a high mortality risk due to underdeveloped immune systems and muscle spasms, which can result in respiratory failure and death. A study in Uganda reported that neonatal tetanus cases caused high mortality rates among newborns [63], supporting this observation. Furthermore, poor people in the study area often use unsterilized tools or contaminated substances to cut the umbilical cord, increasing the risk of bacteria entering the baby's body and potentially leading to adverse outcomes, including death [64].…”
Section: Discussionmentioning
confidence: 58%
“…Neonatal tetanus is also a high mortality risk due to underdeveloped immune systems and muscle spasms, which can result in respiratory failure and death. A study in Uganda reported that neonatal tetanus cases caused high mortality rates among newborns [63], supporting this observation. Furthermore, poor people in the study area often use unsterilized tools or contaminated substances to cut the umbilical cord, increasing the risk of bacteria entering the baby's body and potentially leading to adverse outcomes, including death [64].…”
Section: Discussionmentioning
confidence: 58%
“…This high death rate has been documented most frequently in infants whose symptoms began within the first week of life. Early disease onset may be owing to increased C. tetani bacterial inoculates and younger newborns were physiologically at high risk of death 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Muscle spasms can be very painful and are frequently triggered by stimulation 26 . Tachycardia, bradycardia, blood pressure changes and arrhythmias can all be symptoms of autonomic instability 17 . The spasms last for three to four weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some other reports in the literature claim that people with minor or subtle wounds may potentially contract a tetanus infection 12 . According to our literature review in Table 1, one pediatric patient who developed tetanus did not report an injury or wound 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation